Reconceptualizing ANKUM’s Role in Military Discipline: A Normative and Comparative Reassessment of Command Authority and Justice - Prasetyoandi, Destri; Sulistiani, Lies; Rusmiati, Elis; Aboelazm, Karem Sayed (Universitas Negeri Gorontalo, 2026)
The enforcement of military discipline is essential to operational readiness; however, the normative and ethical foundations of disciplinary authority within the Indonesian National Armed Forces (TNI) remain insufficiently examined. Existing scholarship largely treats ANKUM (Superior Officers Authorized to Impose Punishment) as a procedural or administrative mechanism, leaving a significant gap concerning its ethical legitimacy, normative coherence, and institutional accountability as a command-based disciplinary authority. This article addresses that gap by critically reassessing ANKUM’s role beyond its formal legal mandate. By employing a normative juridical method combined with conceptual and comparative approaches, this study examines Indonesian military disciplinary law alongside selected models from the United Kingdom, Australia, and the United States. The analysis demonstrates that the concentration of discretionary power in ANKUM generates normative vulnerabilities, including inconsistent enforcement, limited procedural safeguards, and ethical tension in balancing command loyalty with justice. The article’s original contribution lies in reconceptualizing military discipline not merely as an instrument of hierarchical control, but as an ethical institution inherent in command responsibility, operationalized through three analytical dimensions: ethical proportionality in sanctioning, institutional accountability mechanisms, and the alignment of disciplinary enforcement with unit cohesion and operational readiness. Grounded in comparative military justice and moral philosophy, the article proposes a reform-oriented framework that enhances legal legitimacy and strengthens ethical command within democratic civil–military relations